Awareness of the risks and dangers of social networking: exploration on four types of Malaysian secondary schools - Thang, Siew Ming; Ng, Lay Shi; Adzuhaidah M. Taha (Penerbit Universiti Kebangsaan Malaysia, 2020)
While social networking (SN) undoubtedly plays a vital role in the life of today's teenagers, its risks cannot be overlooked. SN can be a pervasive technology which can result in "risky behaviours". Issues linked to such behaviours have been investigated in a variety of contexts abroad (however, less so in the Malaysian context). The study aims at investigating Malaysian Secondary school students’ awareness of the risks and dangers of SN. A quantitative approach involving a questionnaire survey was used to collect data. The questionnaire was designed to elicit information from the students regarding their awareness of the risks and dangers as well as abuse of the SN systems such as cyberbullying, harassment, sexting etc. The questionnaire was distributed to all available Form Four students from four selected schools in the Klang Valley and Selangor i.e. an urban school, a suburban school, a rural school and an elite school. The quantitative study was conducted on 562 students from the four schools. Descriptive and inferential statistics were used in analysing the data. The findings revealed that there was no rural-urban divide with regard to awareness of the risks and dangers involved in SN. Students in general seemed to be aware of the risks and dangers of SN. Likewise, there was no clear rural-urban divide regarding awareness of privacy issues. However, there was some ignorance regarding certain risks. For example, they were generally not aware that it was not possible to stay anonymous online. There were also some marked differences across school-types.